Tricuspid Valve Replacement: An Analysis of Risk Factors and Outcomes - ARSAN, SİNAN (GEORG THIEME VERLAG KG, 2008)
Background: Tricuspid valve replacement (TVR) is rarely performed and is associated with a high morbidity and mortality. We report our experience with TVR and related adverse events. Methods: Between January 1996 and December 2007, 35 patients underwent TVR with mechanical (n = 33) or bioprosthetic (n = 2) valves. Twentynine patients underwent concomitant cardiac procedures. Results: All patients completed follow-up (mean 47 months). Thirty-day mortality was 20% (n = 7). Risk factors included perioperative low arterial blood pressure (p = 0.000), New York Heart Association (NYHA) functional class III or IV (p = 0.001), severe pulmonary hypertension (pulmonary arterial pressure greater than 60 mmHg) (p = 0.000), hepatic dysfunction (p = 0.000), ascites (p = 0.003), and reoperation (p = 0.015). Late mortality occurred in five patients. Valve-related complications included bleeding (n = 1) and stroke (n = 1). Kaplan-Meier estimates of 1-, 5and 10-year survival (including early mortality) and event-free survival were 77.1%, 60%, and 54.3% and 91.1%, 80.6%, and 55.9%, respectively. Severe pulmonary hypertension was the only predictor of late mortality (p = 0.001). Among survivors, the mean NYHA class improved from 2.8 to 1.1 (p = 0.000). Conclusions: Although early outcome after TVR is suboptimal, long-term survival and functional improvement is satisfactory.\
Keywords: heart valve surgery; cardiovascular surgery; heart disease